2010
DOI: 10.1007/s12665-010-0537-z
|View full text |Cite
|
Sign up to set email alerts
|

Mercury speciation in soil in vicinity of coal beds using sequential extraction

Abstract: The sequential extraction procedure was proposed and used to study of mercury speciation in real samples of soil. Samples of soil profiles together with bedrock and coal were taken from sampling spots in the vicinity of surficial coal beds in an area with natural coal outcrops. The proposed sequential extraction procedure involves the following fractionation: organic mercury compounds, extractable mercury in an acidic medium, mercury bound to humic substances, elemental Hg and mercury bound to complexes, HgS a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 18 publications
1
2
0
Order By: Relevance
“…Trace Hg analysis revealed that mercury contents in the Faroese coal are generally low. Similar or slightly higher concentrations were also reported from Palaeozoic bituminous coals from the Czech Republic (Coufalík et al, 2011). This observation supports the idea that no correlation exists between mercury content and coal rank (Kilgroe et al, 2002).…”
Section: Mercury Speciation Behaviour and Environmental Impactsupporting
confidence: 86%
“…Trace Hg analysis revealed that mercury contents in the Faroese coal are generally low. Similar or slightly higher concentrations were also reported from Palaeozoic bituminous coals from the Czech Republic (Coufalík et al, 2011). This observation supports the idea that no correlation exists between mercury content and coal rank (Kilgroe et al, 2002).…”
Section: Mercury Speciation Behaviour and Environmental Impactsupporting
confidence: 86%
“…The sequential extraction procedures designated as extraction procedure A (Zverina et al 2014) and extraction procedure B (Fernandez‐Martinez et al 2014) were used for fractionation analyses of mercury in the soil samples. Procedure A (Zverina et al 2014) is based on the method published by Bloom et al (2003) and Coufalik et al (2011).…”
Section: Methodsmentioning
confidence: 99%
“…The modes of occurrence of trace elements was studied by four-step sequential extraction test, which was originally developed to analyze soil samples and later modified to analyze coal. The methodology follows the previous studies [4][5][6][7], as shown in Fig. 1.…”
Section: Methodsmentioning
confidence: 99%